Education and retirement: Does University education at mid-age extend working life? - Anders Stenberg; Olle Westerlund (IZA Journal of European Labor Studies, 2013)
To our knowledge, this paper provides the first study evaluating the effects of higher education for adults on the timing of retirement. Using detailed longitudinal population register data 1982-2010, we track first-time enrollees in higher education in 1992-1993. Our sample is aged 42-55 at the time of enrollment and thus aged 60-73 in 2010. We find that higher education increases labor market survival rates when aged 61-66 by about 5 percentage points. The estimates represent relatively large effects. Tentative calculations indicate that if enrollment occurs at age 42, the retirement delay represents about one percent in yearly earnings returns per year of tertiary education.
Keywords: H52; H55; I28; 330; Human capital; Education; Labor supply; Retirement; Pensions